Perilaku Konsumen dalam Pembelian Daging Ayam Broiler Secara Online di Era New Normal Covid-19 Kota Bandar Lampung, Lampung - Husain, Abu Haris; Indriani, Yaktiworo; Hudoyo, Agus (Universitas Galuh, 2024)
Consumers tend to experience changes in attitudes and satisfaction towards purchasing broiler chicken meat in the new normal era. This research was conducted using a survey method which aims to determine consumer attitudes and levels of satisfaction by paying attention to what attributes consumers consider before buying broiler chicken meat in the new normal era. The number of samples in this study was 116 respondents. Research data was analyzed conjointly which describes consumer attitudes based on evaluation of various product attributes and Importance Performance Analysis (IPA) to measure attributes that influence consumer satisfaction with purchasing broiler chicken meat. Based on conjoint analysis, it shows that consumer attitudes towards broiler chicken meat in the new normal era are in a very good direction with the attributes most liked by household consumers in Bandar Lampung, namely halal labels, meat texture, type of purchase, price of chicken, aroma and skin color. . The combination of broiler chicken attributes that Bandar Lampung household consumers like is cheap price, not rancid aroma, shiny yellowish red skin color, chewy texture, halal label, and online purchase type. The level of consumer satisfaction based on the consumer satisfaction index for broiler chicken meat is 91.39 percent which is in the very satisfied category. The level of consumer satisfaction with the performance attributes of texture, type of purchase, halal and color of broiler chicken meat is in the range of 4.18-4.28, falling into the very satisfied category. Meanwhile, consumer satisfaction with the performance attributes of price and aroma of broiler chicken meat is in the range of 4.07 and 4.06, which is in the satisfied category.